This doesn't look nice...

Algebra Level 5

Given that the value of

i = 1 1 × 4 × 7 × × ( 3 i 2 ) 6 × 12 × 18 × × 6 i \sum _ { i = 1 } ^ { \infty } \frac {1 \times 4 \times 7 \times \ldots \times ( 3i - 2 ) } { 6 \times 12 \times 18 \times \ldots \times 6i }

can be expressed in the form a 15 b 15 \sqrt [ 15 ] { a } - \sqrt [ 15 ] { b } , where a a and b b are positive integers, find the smallest possible value of a b ab .


The answer is 32.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Nick Diaco
Dec 22, 2014

You guys are going to hate yourselves for how simple this is: upon close observation, it is possible to note that each coefficient of the sum is of the form ( 1 2 ) i ( 1 3 i ) \left(- \frac{1}{2} \right)^i { -\frac{1}{3} \choose i } for integer values of i 1 i \ge 1 . This prompts us to consider the expansion of the binomial ( 1 + x ) 1 3 (1+x)^{-\frac{1}{3}} , which is 1 x 3 + 2 x 2 9 14 x 3 81 + 35 x 4 243 1 - \frac{x}{3} + \frac{2 x^2}{9} - \frac{14x^3}{81} + \frac{35x^4}{243} - \ldots

If we let x = 1 2 x = -\frac{1}{2} , the above expansion becomes

1 + i = 1 1 × 4 × 7 × × ( 3 i 2 ) 6 × 12 × 18 × × 6 i = ( 1 1 2 ) 1 3 = 2 3 . 1 + \sum _ { i = 1 } ^ { \infty } \frac {1 \times 4 \times 7 \times \ldots \times ( 3i - 2 ) } { 6 \times 12 \times 18 \times \ldots \times 6i } = (1-\frac{1}{2})^{-\frac{1}{3}} = \sqrt[3]{2} .

It follows that our summation is equal to 2 3 1 = 32 15 1 15 \sqrt[3]{2} - 1 = \sqrt[15]{32} - \sqrt[15]{1} , so our answer is 32 \fbox{32}

\\

A very similar problem can be found here .

You're right. I hate myself now.

Stefan Chircop - 6 years, 2 months ago
Abhishek Sinha
Dec 19, 2014

Consider the following binomial expansion 2 1 / 3 = ( 1 1 2 ) 1 3 = 1 + i = 1 1 i ! 2 i r = 1 i ( 1 3 + r 1 ) = 1 + i = 1 1 i ! 6 i r = 1 i ( 3 r 2 ) 2^{1/3}=(1-\frac{1}{2})^{-\frac{1}{3}}=1+\sum_{i=1}^{\infty}\frac{1}{i!2^i}\prod_{r=1}^{i}(\frac{1}{3}+r-1)\\=1+\sum_{i=1}^{\infty}\frac{1}{i!6^i}\prod_{r=1}^{i}(3r-2) Thus, i = 1 1 i ! 6 i r = 1 i ( 3 r 2 ) = 2 1 / 3 1 = 32 15 1 15 \sum_{i=1}^{\infty}\frac{1}{i!6^i}\prod_{r=1}^{i}(3r-2)=2^{1/3}-1=\sqrt[15]{32}-\sqrt[15]{1}

Can u explain it bro?

Kudou Shinichi - 6 years, 5 months ago

Log in to reply

Pl post a detailed solution. Thanks.

Prabir Chaudhuri - 6 years, 5 months ago

It is binomial expansion.

Joel Tan - 6 years, 1 month ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...